Pala dan Cengkeh Di antara Jejak Sejarah, Batik dan Identitas - Lois Denissa (Humanitas (Jurnal Psikologi), 2022)
Nutmeg and Clove are native plants to Indonesia, growing in the islands of Banda and Maluku (Siswanti, 2022: 80) Both are spice commodities of fantastic value of the 15th century in world trade, one kilogram of nutmeg or cloves equivalent to one kilogram of pure gold, primadonnas that are highly targeted by the nations. Spanish, Portuguese, Dutch and British raced for months to year find the source of spices, monopolize trade and snatch huge profits. Nutmeg and cloves have become the identity of Maluku, ironically this identity actually led Europeans to colonize. Nutmeg and cloves at that time became primadonna because of its powerful power in the procurement of food, cosmetics and health. This historical trace has been inscribed in batik motifs to perpetuate the identity of the Banda and Maluku islands. This research uses qualitative analytical methods to the spice phenomenon of nusantara that occurred in the past and the efforts of the Moluccas in maintaining their identity in the shape of batik. The aim of the study is to instill awareness of the younger generation and put nutmeg and cloves back as commodities of international value. Extracting the benefits of nutmeg and cloves and its promotion in batik motifs will build a careful understanding and develop the spirit of the same collective identity. Batik Nutmeg and Cloves have a strong historical foundation in cementing the identity of the oral and intangible heritage of humanity established by Unesco.